The destruction of cities in the ancient Greek world (Cambridge ; New York)
xiv, 361 sayfa
Keywords: “From the Trojan War to the sack of Rome by Alaric, from the fall of Constantinople to the bombing of European cities in World War II and now the devastation of Syrian towns filmed by drones, the destruction of cities and monuments and the slaughter of civilian populations are among the most dramatic events in world history. Since the beginning of literature and figurative art, authors, storytellers, bards, poets, artists, tragedians, historians, art historians, and archaeologists have been fascinated by the evocative power of destructions and ruined cities.” --